2021
DOI: 10.3390/ma14154147
|View full text |Cite
|
Sign up to set email alerts
|

Does Simulated Porcelain Firing Influence Corrosion Properties of Casted and Sintered CoCr Alloys?

Abstract: The aim of the study was to evaluate how heat processing used for dental porcelain firing influences the surface properties of sintered and casted CoCr alloy. Two CoCr alloys, Soft Metal LHK (milling in soft material and sintering) and MoguCera C (casting), were used for the study. The samples were examined using SEM–EDS before and after heat treatment. Next, corrosion examinations (Ecorr, jcorr, polarization curve, Ebr) were performed. Finally, the samples were evaluated under SEM. Based on the results, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The results of the work by Tuncdemir et al [56], evaluating the corrosive behavior of Ni-Cr alloys, as well as Co-Cr after porcelain firing, showed that multiple firings also reduce the corrosion resistance of Cr-Co alloys. Similarly, in the works of Rylska et al [57,58] the porcelain firing simulation of Co-Cr alloys obtained by CST, MSM and SLM methods, caused, in each case, a decrease in corrosion resistance. It is essential that the most significant decrease in corrosion resistance was recorded for as-cast samples that presented the most tremendous variation in the composition of oxides on the surface after HT.…”
Section: Corrosion Properties and Immersion Test Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The results of the work by Tuncdemir et al [56], evaluating the corrosive behavior of Ni-Cr alloys, as well as Co-Cr after porcelain firing, showed that multiple firings also reduce the corrosion resistance of Cr-Co alloys. Similarly, in the works of Rylska et al [57,58] the porcelain firing simulation of Co-Cr alloys obtained by CST, MSM and SLM methods, caused, in each case, a decrease in corrosion resistance. It is essential that the most significant decrease in corrosion resistance was recorded for as-cast samples that presented the most tremendous variation in the composition of oxides on the surface after HT.…”
Section: Corrosion Properties and Immersion Test Resultsmentioning
confidence: 73%
“…Some researchers find a higher level of ions released before the HT [54], while others' results indicate no differences in corrosion resistance [55]. However, several works reported the reduced corrosion resistance after HT [56][57][58].…”
Section: Introductionmentioning
confidence: 98%